2001
DOI: 10.1123/ijsnem.11.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Profiles of Elite American Heptathletes

Abstract: This study characterized body composition profiles of elite American heptathletes and cross-validated skinfold (SKF) and bioelectrical impedance analysis (BIA) field method equations for estimation of percent body fat (%Fat) using dual energy x-ray absorptiometry (DXA) as the criterion. Weight, height, fat mass (FM), fat-free mass (FFM), bone mineral density (BMD), and %Fat were measured in 19 heptathletes using standard measurement protocols for DXA, SKFs and BIA. The ages, heights, and weights were respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 40 publications
(28 reference statements)
1
6
0
2
Order By: Relevance
“…Moreover, applying the derived equations to a separate sample of 24 athletes, they predicted a fat mass with a TE of 2.9%. Houtkooper et al 28 reported that BIA overestimated the average BF% of elite female heptathletes by 4.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, applying the derived equations to a separate sample of 24 athletes, they predicted a fat mass with a TE of 2.9%. Houtkooper et al 28 reported that BIA overestimated the average BF% of elite female heptathletes by 4.4%.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63][64][65][66][67][68] For male and female athletes participating in various sports and activities across multiple age ranges, BIA produced FFM standard error of estimate values ranging from 1.1 to 2.6 kg, but significant mean differences were observed in several studies showing a significant overestimation, as well as underestimations. [61][62][63][64][65][66][67][68] Many studies have compared BIA with anthropometric equations with varying results. 35,[69][70][71][72] However, all studies have shown good agreement between methods.…”
Section: Validation Studies and Equationsmentioning
confidence: 99%
“…The little levels of body fat mass, optimal level of water mass and FFBM and WFBM for soccer players influence successful performance within the competition and body mass structure are very significant determinants of competitive success of soccer players. FFBM, FFBMI, WFBM, WFBMI may advantageously affect performance, requiring translocation of body mass, such as in running, jumping or rotation of the body around an axis (Houtkooper, 2001;Sinning, 1996;our unpublished data, 2005).…”
Section: Discussionmentioning
confidence: 91%